Los delitos y los castigos en el período colonial, frente a la legislación actual panameña - Reyes Peña, Pastor Conrado; Arango Durling, Virginia (Panamá : Universidad, 2024)
This research work has to do with the crimes and punishments that occurred during colonial times here in America, and how the authorities of the time punished them. At the same time, we can read how they evolved over time. We will also be nourished with the knowledge that will be learned, and how those same crimes and punishments are applied in the penal code of the Republic of Panama, or on the contrary they no longer have applicability in this contemporary world, where what must prevail are the Human Rights, and not the arbitrariness that took place in the colony.
"Trabajo de graduación para optar al titulo de Licenciatura en Derecho y Ciencias Políticas": -- Página de título.
Resumen en inglés.
Keywords: DERECHO PENAL -- PANAMA -- HISTORIA; DERECHO COLONIAL ESPAÑOL -- AMERICA -- HISTORIA; DELITOS -- HISTORIA; PENAS -- HISTORIA; CASTIGOS CORPORALES -- HISTORIA; ADMINISTRACION DE JUSTICIA PENAL -- ESPAÑA -- HISTORIA; ADMINISTRACION DE JUSTICIA PENAL -- PANAMA; DERECHO -- TESIS Y DISERTACIONES ACADEMICAS; ESPAÑA -- COLONIAS -- AMERICA -- LEGISLACION